1989
DOI: 10.1161/01.hyp.13.3.206
|View full text |Cite
|
Sign up to set email alerts
|

Red-cell sodium-lithium countertransport and fractional excretion of lithium in normal and hypertensive humans.

Abstract: To examine the relations between erythrocyte sodium-lithium countertransport and renal proximal tubular sodium handling, we measured countertransport, and then subjected 30 normal and 32 hypertensive subjects, both white and black, to provocative maneuvers of volume expansion and contraction. The fractional excretions of sodium and lithium were measured simultaneously. In agreement with previous studies, we found that countertransport in erythrocytes was elevated in hypertensive patients compared with normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Moreover, volume expansion caused a greater natriuresis and greater increase in fractional excretion of lithium among the hypertensive patients. It is suggested that hypertensive patients do not have increased proximal tubular sodium reabsorption and that the exaggerated natriuresis often observed in hyper-tension is a result of increased distal tubular sodium delivery (34). These conclusions were also confirmed in another paper (35).…”
Section: Ion Exchangersmentioning
confidence: 61%
See 1 more Smart Citation
“…Moreover, volume expansion caused a greater natriuresis and greater increase in fractional excretion of lithium among the hypertensive patients. It is suggested that hypertensive patients do not have increased proximal tubular sodium reabsorption and that the exaggerated natriuresis often observed in hyper-tension is a result of increased distal tubular sodium delivery (34). These conclusions were also confirmed in another paper (35).…”
Section: Ion Exchangersmentioning
confidence: 61%
“…The hypertensive patients had an increased Na + -Li + CT. The fractional excretion of lithium was higher in those with elevated BP, despite similar baseline values for the fractional excretion of sodium between normotensive and hypertensive individuals (34). Moreover, volume expansion caused a greater natriuresis and greater increase in fractional excretion of lithium among the hypertensive patients.…”
Section: Ion Exchangersmentioning
confidence: 79%
“…25 Significant correlations between lithium clearance and rates of Na + -Li + countertransport have been reported by some authors in young patients with essential hypertension 10 and in the offspring of hypertensive patients 11 but have not been confirmed by other workers. 44 - 45 The discrepancies between these studies could be accounted for, at least in part, by differences in age, race, and clinical characteristics of the patients studied. Although caution must be used in the interpretation of lithium clearance, our findings support the view that hypertensive patients with high Na + -Li + countertransport reabsorb more sodium, which could explain their expanded sodium pool.…”
Section: % Hypertension Vol 18 No 2 August 1991mentioning
confidence: 99%
“…16,[20][21][22][23][24] Weder first reported that 14 untreated hypertensive patients had a lower FE Li than 31 normotensive subjects (13.96% versus 17.75%; P<0.01). 20 In a later study, Burnier et al found that 13 untreated whitecoat hypertensive patients but not 53 untreated hypertensive patients had significantly lower FE Li than 48 normotensive subjects (11.6% versus 15.4% versus 17.0%).…”
Section: Discussionmentioning
confidence: 99%